Particulate matter (PM10) induces metalloprotease activity and invasion in airway epithelial cells. Issue 3 (17th September 2015) - Morales-Bárcenas, Rocío; Chirino, Yolanda I.; Sánchez-Pérez, Yesennia; Osornio-Vargas, Álvaro Román; Melendez-Zajgla, Jorge; Rosas, Irma; García-Cuellar, Claudia María
Highlights PM10 induces metalloproteases expression and activity. PM10 induces invasiveness. PM10 downregulates E-Cadherin/β-Catenin expression.